Antiviral Effect of Ethanolic Extract of Red Ginger Rhizome (Zingiber officinale Linn var. rubrum) Against Dengue Virus In Vitro - Natasha Ninda Pramalista; Afiono Agung Prasetyo; Ratih Dewi Yudhani (Nexus Biomedika, 2017)
Introduction: Dengue virus is a type of virus that causes various reactions, from asymptomatic infection to harmful manifestations, such as dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). Currently, the treatments of DHF cases have been limited to symptomatic and supportive therapies only. Therefore, it is necessary to develop new strategies in facing these cases. One of them is by using natural ingredients with antiviral potential. The aim of this study is to understand the antiviral effects of the ethanol extract of red ginger rhizome (Zingiber officinale Linn var. rubrum) against dengue virus in vitro. Methods : The subject of this research was Dengue virus serotype 2 strain New guinea C (DENV-2 NGC) which was infected into Huh-7 cell line. The research was divided into 2 parts. The first was inhibition test of the extract against DENV-2 which was assessed by average of infectivity percentage with Focus Forming Unit assay method. The second was toxicity test of the extract in Huh 7 cells which was assessed by average of viability percentage by MTT assay method. The herb extract effective as a Dengue antivirus was defined by average infectivity percentage of ? 20% and average viability percentage of > 50%. Results: Ethanolic extract of Red Ginger rhizome (Zingiber officinale Linn var. Rubrum) with concentration 80, 40, 20, 10, 5, 2.5 g/ml had average percentage of infectivity respectively: 9.2% ; 25.3% ; 32.3% ;47.5% ; 66.6% ; 73.4%. While the average percentage of viability were: 92.2% ; 94.3% ; 96.7 % ; 99.6% ; 102.7% ; 105.9%. Conclusions: Ethanolic extract of rhizome Red Ginger (Zingiber officinale Linn var. Rubrum) is not effective in inhibiting the replication of dengue virus serotype DENV-2 in vitro because it has the average infectivity percentage ? 20 and has no toxic effects on cells Huh-7 because it has the average viability percentage > 50. Key Words: Zingiber officinale Linn var. rubrum, Dengue virus, DENV-2, Huh-7 cell line.